Quantifying patterns and select correlates of the spatially and temporally explicit distribution of a fish predator (Blue Catfish, Ictalurus furcatus) throughout a large reservoir ecosystem - Peterson, Zachary James (Kansas State University, 2015)
Understanding how and why fish distribution is related to specific habitat characteristics underlies many ecological patterns and is crucial for effective research and management. Blue Catfish, Ictalurus furcatus, are an important concern for many fisheries agencies; however, lack of information about their distribution and habitat use remains a hindrance to proper management. Here, over all time periods and across months, I quantified Blue Catfish distribution and environmental correlates of distribution in Milford Reservoir, the largest reservoir in Kansas. I tested relationships among acoustically tagged Blue Catfish and three groups of variables postulated to influence Blue Catfish distribution in the literature (i. localized microhabitat variables, ii. larger-scale mesohabitat variables, iii. biotic variables). Blue Catfish were consistently aggregated in two locations of the reservoir across five months during summer and fall, 2013. Using multiple linear regression and an information theoretic model selection approach, consistent correlates of distribution included localized, microhabitat variables (i.e., dissolved oxygen, slope) larger-scale, mesohabitat variables (i.e., distance to channel, river kilometer from the dam) and a biotic variable (i.e., Secchi depth). This research identified which 5 of the 12 variables identified in the literature were most influential in determining Blue Catfish distribution. As a guide for future hypothesis generation and research, I propose that Blue Catfish distribution was driven by three ecologically-relevant tiers of influence. First, Blue Catfish avoided extremely low dissolved oxygen concentrations that cause physiological stress. Second, Blue Catfish aggregated near the channel, an area of bathymetric heterogeneity that may offer a foraging advantage. Third, Blue Catfish aggregated near low Secchi depths, shown here to be associated with increased productivity and prey abundance. Building on my results, future research into the distribution and habitat use of Blue Catfish should incorporate aggregated distributions of fish into research designs, focus on how both small and large scale relationships interact to produce patterns of distribution, and explore further the mechanisms, consequences, and interactions among the three tiers of influence identified here.
Keywords: Blue catfish; Ictalurus furcatus; Habitat use; Information theoretic approach; Reservoir ecosystem; Biology (0306); Ecology (0329); Natural Resource Management (0528)